Sarcomatoid Intrahepatic Cholangiocarcinoma: A Case Report - Cuiwei Wang, MD, Xin-Hua Ye, MD (Advanced Ultrasound in Diagnosis and Therapy, 2023)
Conventional two-dimensional ultrasonography revealed a hypoechoic mass in the liver of a middle-aged male patient. Enhanced ultrasound suggested intrahepatic cholangiocarcinoma. Enhanced MRI confirmed it as liver cancer. The patient underwent partial liver resection and was pathologically diagnosed as sarcomatoid intrahepatic cholangiocarcinoma. Pulmonary infection occurred one month after surgery. Chest CT suggested left rib metastasis and then radiotherapy was performed. The patient was treated with Lenvatinib after discharge. No recurrence was observed within 36 months. He survived much longer than other patients reported in the literature. The survival of patients with intrahepatic cholangiocarcinoma can be prolonged through early detection and treatments of surgery, radiotherapy and targeted therapy.